2016
DOI: 10.3892/ol.2016.4859
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial cells and their progenitors in acute myeloid leukemia

Abstract: Abstract. Acute myeloid leukemia (AML) is an aggressive hematological malignancy characterized by the accumulation of immature myeloid progenitor cells in the bone marrow. Studies are required to investigate the prognostic and predictive value of surrogate biomarkers. Given the importance of angiogenesis in oncology in terms of pathogenesis as well as being a target for treatment, circulating endothelial cells (CECs) and endothelial progenitor cells (EPCs) are promising candidates to serve as such markers. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Moreover, EPCs (including CECs) are increased in the peripheral blood of patients with various cancers, such as multiple myeloma [228], acute myeloid leukaemia [229, 230], nonsmall cell lung cancer (NSCLC) [231], hepatocellular carcinoma [232, 233], breast cancer [234–236], ovarian cancer [237], chronic lymphocytic leukaemia (CLL) [238], renal cell carcinoma (RCC) [239, 240], and endometrial cancer [241]. CECs have been implicated in tumour progression and aggressiveness [230, 231, 235, 237, 238, 240, 241]. Furthermore, in malignant breast carcinoma, EPCs are resistant to the cytokine TNF- α , which is responsible for inducing apoptosis [242].…”
Section: Current Prospectsmentioning
confidence: 99%
“…Moreover, EPCs (including CECs) are increased in the peripheral blood of patients with various cancers, such as multiple myeloma [228], acute myeloid leukaemia [229, 230], nonsmall cell lung cancer (NSCLC) [231], hepatocellular carcinoma [232, 233], breast cancer [234–236], ovarian cancer [237], chronic lymphocytic leukaemia (CLL) [238], renal cell carcinoma (RCC) [239, 240], and endometrial cancer [241]. CECs have been implicated in tumour progression and aggressiveness [230, 231, 235, 237, 238, 240, 241]. Furthermore, in malignant breast carcinoma, EPCs are resistant to the cytokine TNF- α , which is responsible for inducing apoptosis [242].…”
Section: Current Prospectsmentioning
confidence: 99%
“…were defined by the phenotype of CD34 þ CD133 þ CD45and quantified as a percentage of the total white blood cells population (%HSCs/WBCs). The EPCs were defined by the phenotype of CD144 þ CD34 þ CD133 þ CD45 -, and quantified as percentage from the HSCs subpopulation (% EPCs/ HSCs) [13,32,33].…”
Section: Flow Cytometric Detection Of the Circulating Hematopoietic Smentioning
confidence: 99%
“…17,58 A retrospective controlled study involving patients with acute myeloid leukemia (AML) showed a correlation between EPC and CEC counts and treatment response. 59 At the initial diagnosis stage, CEC and EPC levels of AML patients were significantly higher than those of the control group, and these levels then decreased after chemotherapy. Although both cell counts correlated with prognosis, it was suggested that a higher CEC count might better reflect the metabolic status and treatment response of patients with AML malignancies.…”
Section: Cell-based Biomarkersmentioning
confidence: 86%